Nghiên cứu ảnh hưởng của dòng bão hòa trong nú t giao đèn tín hiệu tạ i thà nh phó Nha Trang - Trần, Quang Duy; Nguyễn, Tuấn Khang; Huỳnh, Trọng Tiến; Thái, Thị Kim Thoa; Trịnh, Tuấn Hùng (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2026)
Saturation flow plays an important role in evaluating the performance of signalized intersections, with clear differences across regions. As traffic demand increases, signal design based on saturation flow has become an important research topic. However, most studies to date have primarily focused on large cities such as Hanoi and Ho Chi Minh City. Therefore, this study focuses on assessing the impact of saturation flow at signalized intersections in Nha Trang city. The study analyzes the relationship between saturation flow and lane width through surveys at nine intersections during peak hours. The second-degree nonlinear model shows a high fit with real data. The application of this model helps improve traffic flow. The research results provide a foundation for improving signal design in Nha Trang and other areas with similar traffic conditions